2012
DOI: 10.3389/fpsyg.2012.00372
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of time versus money in product evaluation

Abstract: The common saying “time is money” reflects the widespread belief in many people’s everyday life that time is valuable like money. Psychologically and neurophysiologically, however, these concepts seem to be quite different. This research replicates prior behavioral investigations by showing that merely mentioning “time” (compared to merely mentioning “money”) leads participants to evaluate a product more positively. Beyond this finding, the present functional magnetic resonance imaging (fMRI) experiment provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 119 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…As such, these results also contribute to the time and money literature. The findings in this area of research point to money-minded people being more disconnected from the products they own (Mogilner and Aaker 2009;Lehmann and Reimann 2012) and more distant from social others (e.g., Vohs et al 2006;Mogilner 2010). Building upon this body of work and extending the work of Teng et al (2016), I find that money-minded people prefer engaging with humanlike products more than time-minded people when the products clearly serve a functional purpose.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…As such, these results also contribute to the time and money literature. The findings in this area of research point to money-minded people being more disconnected from the products they own (Mogilner and Aaker 2009;Lehmann and Reimann 2012) and more distant from social others (e.g., Vohs et al 2006;Mogilner 2010). Building upon this body of work and extending the work of Teng et al (2016), I find that money-minded people prefer engaging with humanlike products more than time-minded people when the products clearly serve a functional purpose.…”
Section: Discussionmentioning
confidence: 74%
“…After all, thinking about time intensifies the motivation to form social connections, whereas thinking about money primes people to value their independence and create social distance when there is no functional use for the other person. Past research has shown that priming consumers with the concept of time (vs. money) increases satisfaction toward products that these consumers already possess because they are reminded of the personal connection they have formed with the product, rather than the utility of the product (Mogilner and Aaker 2009;Lehmann and Reimann 2012). For objectified products that consumers do not already own, priming time cannot elicit any preexisting feelings of personal con-nection with the product; however, for humanized products, consumers reminded of sociality (through time priming) would be more likely to approach the product for the purpose of forming a social connection compared with consumers reminded of instrumentality (through money priming).…”
Section: Current Researchmentioning
confidence: 99%
“…In examining the reaction of the human brain to the concept of money and phenomena related to money (E.g., monetary rewards and losses) there have been studies, that here are some examples of these studies: In studies [18] to investigate the effect of the concept of money on the human brain, eight studies have been identified in which the concept of money has been associated with changes in the PFC. Also in seven studies, the concept of money activated the cingulate cortex and nucleus accumbens; Six studies have been identified to activate the insula, striatum, and thalamus; The activity of the amygdala, dorsal caudate, and frontal cortex has been observed in five studies; In four studies, the orbitofrontal cortex was affected by money; the midbrain and putamen in three studies; the frontal gyrus, globus pallidus, parietal lobule and precuneus in two studies; and the cerebellar vermis, cerebellum, frontal pole, fusiform gyrus, hippocampus, hypothalamus, operculum, medial temporal lobe, motor cortex, orbital gyrus, and the precentral gyrus have been associated with the concept of money in one study; so that each of these areas is associated with the PFC sector.…”
Section: Economic Inflation and Mbbmentioning
confidence: 99%